Outcomes of Induction Chemotherapy for Head and Neck Cancer Patients: A Combined Study of Two National Cohorts in Taiwan. Issue 7 (February 2016) - Chen, Jin-Hua; Yen, Yu-Chun; Liu, Shing-Hwa; Yuan, Sheng-Po; Wu, Li-Li; Lee, Fei-Peng; Lin, Kuan-Chou; Lai, Ming-Tang; Wu, Chia-Che; Chen, Tsung-Ming; Chang, Chia-Lun; Chow, Jyh-Ming; et al.
Abstract : Abstract: The use of induction chemotherapy (CT) is controversial. We compared the survival of head and neck cancer patients receiving docetaxel- or platinum-based induction CT before concomitant chemoradiotherapy (CCRT) with the survival of those receiving upfront CCRT alone. Data from the National Health Insurance and cancer registry databases in Taiwan were linked and analyzed. We enrolled patients who had head and neck cancer between January 1, 2002 and December 31, 2011. Follow-up was from the index date to December 31, 2013. We included head and neck patients diagnosed according to the International Classification of Diseases, Ninth Revision, Clinical Modification codes 140.0–148.9 who were aged >20 years, at American Joint Committee on Cancer clinical cancer stage III or IV, and receiving induction CT or platinum-based CCRT. The exclusion criteria were a cancer history before head and neck cancer diagnosis, distant metastasis, AJCC clinical cancer stage I or II, receipt of platinum and docetaxel before radiotherapy, an age <20 years, missing sex data, docetaxel use during or after RT, induction CT for >8 weeks before RT, induction CT alone before RT, cetuximab use, adjuvant CT within 90 days after RT completion, an RT dose <7000 cGy, curative head and neck cancer surgery before RT, nasopharyngeal cancer, in situ carcinoma, sarcoma, and head and neck cancer recurrence. We enrolled 10, 721 stage III–IV head and neck cancer patients, with a median follow-up of 4.18 years (interquartile range, 3.25 years). The CCRT (arm 1), docetaxel-based induction CT (arm 2), and platinum-based CCRT (arm 3; control arm) groups comprised 7968, 503, and 2232 patients, respectively. Arm 3 was used to investigate mortality risk after induction CT. After adjustment for age, sex, clinical stage, and comorbidities, the adjusted hazard ratios (aHRs) (95% confidence interval [CI]) for overall death were 1.37 (1.22–1.53) and 1.44 (1.36–1.52) in arms 2 and 3, respectively. In a disease-specific survival rate analysis, aHRs (95% CI) of head and neck cancer-related death were 1.29 (1.14–1.46) and 1.47 (1.38–1.56) in arms 2 and 3, respectively. Compared with CCRT alone, docetaxal- or platinum-based induction CT did not improve survival but increased the risk of all-cause and head and neck cancer-related death. Abstract : Supplemental Digital Content is available in the text